Dairy farmer-labor scheduling model with skills of workers and cows' ability to produce milk - Yusuf Mauluddin; Rosmawati Rosmawati; Putri Silcilia (Journal Industrial Servicess, 2026)
This study develops a Multi-Skill Workforce Scheduling (MSWS) models for dairy farms that accounts for worker skills and cow lactation capacity to maximize milk yield. Using Integer Linear Programming (ILP), two models were proposed: Model 1 with work shifts and Model 2 without shifts. While the shift-based model was limited by excessive computational time, the non-shift model effectively solved real-world scheduling problems. The results revealed a distinctive pattern: highly skilled workers were prioritized for broader scheduling opportunities, whereas less-skilled workers were assigned to cows with higher lactation levels. These findings highlight the potential of ILP-based MSWS to optimize labor allocation in dairy farming.